The predictive effect of subjective well-being and stress on foreign language enjoyment: The mediating effect of positive language education - Ergun, Anna Lia Proietti; Demirdag, Hande Ersoz (FRONTIERS MEDIA SA, 2023)
The present study is the first to investigate the extent to which positive language education can improve foreign language enjoyment in the same learners. At the same time, it explores the relation between life quality variables, subjective well-being (SWB), and stresses that have emerged as important variables to explain foreign language enjoyment (FLE). Participants were 50 native speakers of Turkish, university students, 24 having a high proficiency in one language (English) and 26 having a high proficiency in two languages (French and English). Quantitative data were collected before and after the intervention (3 Good Things and Use your Strength and Virtues in a Creative Way) and qualitative data were collected at the end of the course. The results of pre-test and post-test analysis were not significant FLE (t(49) = -1.3, p > 0.05), SWB (t(49) = -0.58, p > 0.05), and stress (t(49) = -0.7, p > 0.05). Manova with a level of multilingualism as a fixed factor revealed that there was a significant difference in the pre-test and post-test F(3, 46) = 3.49, p < 0.023, Wilk's ? = 0.81, partial eta(2) = 0.023. The Between Subjects' Test reveals a significant difference in the level of SWB (F(1, 48) = 7.04, p < 0.01) and FLE (F(1, 48) = 8.5, p < 0.005), but not for the level of stress (F(1, 48) = 0.29, p < 0.59). A subsequent set of regressions revealed that in pre-test there is not a significant effect of the factors on the dependent variable (R-2 = 0.20, R-2 adjusted = 0.140). The analysis after the intervention shows a significant effect of the SWB on FLE R-2 = 0.35, R-2 adjusted = 0.31, Beta = 0.25, p < 0.002. The analysis of the quantitative data supports the statistical analysis as students report that the intervention has helped to improve the atmosphere in the classroom as well as their general attitude in life and they have learned valuable knowledge about themselves as an added value to the acquisition of the new language. We conclude that positive language education can increase the level of subjective well-being in students and that, in turn, improves the level of positive emotions in the language classroom.
Keywords: positive language education; well-being; foreign language enjoyment; multilingualism; stress; BUILD THEORY; PSYCHOLOGY; EMOTIONS; ANXIETY; POWER; ACHIEVEMENT; VALIDATION; ENGAGEMENT; BENEFITS; LIFE